GAMBARAN PENGETAHUAN MASYARAKAT TENTANG PENGGUNAAN MULTIVITAMIN DAN SUPLEMEN KESEHATAN SELAMA PANDEMI COVID-19 - Fina Aryani; Desmalia Desmalia; Husnawati Husnawati; Septi Muharni; Mira Febrina; Anugrah Humairah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Increasing number of cases of COVID-19 currently requiring the community to make more efforts to carry out various preventive efforts. One of the efforts that can be done to prevent COVID-19 is to maintain and increase the body's immunity which can be assisted by the use of multivitamins and health supplements. This study aims to examine public knowledge about the use of multivitamins and health supplements in Pekanbaru family pharmacies during the COVID-19 pandemic. This research is a descriptive observational study with concurrent data collection techniques through online questionnaires. The sampling technique in this study was carried out by non-probability sampling with purposive sampling method. The sample in this study is the people of Pekanbaru City who meet the inclusion criteria with a total of 110 respondents. Data analysis in this study used univariate analysis which aims to explain or describe the characteristics of each research variable, so that the results obtained that people who have good knowledge are 54.64%, people who have sufficient knowledge are 43.63%, and people who have good knowledge have less knowledge is as much as 1.81%. The high percentage of respondents with good knowledge shows that most people in Pekanbaru City already have good knowledge about the use of multivitamins and health supplements during the COVID-19 pandemic.